Prevalencia de enfermedades en el adulto mayor residente del Centro Gerontológico MIES Los Rosales de Santo Domingo de los Tsáchilas 2015 - Valarezo Pinargote, Amarilis Rocío (2015)
The aging process differs according to social status. Because it is necessary to continue developing alternative proposals and spaces to improve the quality of life through plans, programs and projects where older people are active entities in the process of social inclusion with family and society. Hence the question arises us How does the knowledge of the diseases prevalent in the care provided to the Elderly resident of the Rosales Mies geriatric center of Santo Domingo Province of Tsachilas 2015 ". Therefore the objective is to "determine the prevalence of chronic diseases of the elderly and how these influence in the activities of residents of Gerontological center Mies Rosales Santo Domingo 2015". After analyzing the same came to the following conclusions: The staff has a lack of the most common diseases in older adults, so do not run good practice for prevention and show limited knowledge about risk factors and geriatric syndromes. The Center has the infrastructure required to ensure living conditions for the elderly, but no one natural area conducive to healthy recreation, does not have the necessary medical personnel to ensure medical care in the evenings and on weekends , which affects the quality of service. It was recommended that the MIES must strategize permanent improvement and updated mandatory for staff must complete the required personnel to ensure the consistent and systematic attention, Trace strategies and plans that project activities liked by older adults and thus encourage the active aging. implement actions involving the family of the elderly in improving their emotional state. And finally the implementation of the training plan and other personnel informal caregivers, with emphasis on the family of the elderly. KEYWORDS: Geriatric Care Patient Gerontology, Geriatric Care , Aging , Social Gerontology , Gerontology Cultural .